2020
DOI: 10.1002/onco.13516
|View full text |Cite
|
Sign up to set email alerts
|

A Timely Oral Option: Single-Agent Vinorelbine in Desmoid Tumors

Abstract: Introduction. Desmoid tumors (DT) are rare collagen-forming tumors that can exhibit locally aggressive patterns of behavior. The aim of this study was to evaluate the efficacy and safety of treatment of DT with single-agent oral vinorelbine. Materials and Methods. A retrospective review of patients treated with vinorelbine 90 mg orally on days 1, 8, and 15 of a 28-day cycle from January 2004 to July 2019 was performed. Response was assessed using RECIST version 1.1. Descriptive statistics were employed. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Low-dose MTX/VNL or VBL chemotherapy is effective and minimally toxic regimen but has significant impact on quality of life (QoL) for the lengthy duration of treatment. Single agent oral vinorelbine has a disease control rate of 86% with an excellent toxicity profile (46,64). Low dose chemotherapy regimens are an effective, safe, and affordable choice that can offer long term symptoms and disease control, however responses are delayed compared to other agents; their use is especially common in the pediatric and young adults' population for the well understood toxicity profile.…”
Section: Chemotherapymentioning
confidence: 99%
“…Low-dose MTX/VNL or VBL chemotherapy is effective and minimally toxic regimen but has significant impact on quality of life (QoL) for the lengthy duration of treatment. Single agent oral vinorelbine has a disease control rate of 86% with an excellent toxicity profile (46,64). Low dose chemotherapy regimens are an effective, safe, and affordable choice that can offer long term symptoms and disease control, however responses are delayed compared to other agents; their use is especially common in the pediatric and young adults' population for the well understood toxicity profile.…”
Section: Chemotherapymentioning
confidence: 99%
“…Several recent retrospective studies of oral singleagent vinorelbine have reported moderate response and clinical benefit rates in patients with DT. 68,69 Among 90 adults who had DT treated with oral vinorelbine with or without antiestrogen therapy, the best responses were 29% PR, 57% SD, and 14% progressive disease. 69 Concomitant antiestrogen therapy was associated with a significantly longer time to treatment failure in women (p = .03).…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“…No patient experienced at least grade 3 toxicity. Common toxicities were grades 1–2 nausea (48%), fatigue (31%), and diarrhea (14%) [19].…”
Section: Systemic Treatment Of Desmoid-type Fibromatosismentioning
confidence: 99%